Saint Augustine and the Fall of the Soul: Beyond O’Connell and his Critics. By Ronnie J. Rombs - Lane, Margaret (The journal of theological studies, 2009)
Augustine never felt compelled to decide definitively in favour of any one of the four theories of the origin of the soul that prevailed in late antiquity—that it was fallen, sent, propagated, or created—even though the fallen-soul theory cohered best with the idea of original sin, which was also prevalent at that time, among both Christians and non-Christians alike, and which Augustine did have to confront. He did at one stage decisively reject the fallen-soul theory on the grounds that it was incompatible with Scripture (Rom. 9:11), but Robert O’Connell believed that Augustine subsequently returned to favour the fallen-soul theory in his later years.